Association of vesicoureteral reflux and gastroesophageal reflux disease in children: A population-based study - Hosier, Gregory W. (Can Urol Assoc J, 2020)
INTRODUCTION: Practitioners have anecdotally hinted at a possible association between gastroesophageal reflux disease (GERD) and vesicoureteral reflux (VUR). We sought to identify an association in diagnosis between GERD and VUR using a population-based dataset in a well-defined geographic area covered by a single-payer healthcare system. METHODS: A retrospective review of individuals aged 0–16 years registered in the Nova Scotia Medical Service Insurance database from January 1997 to December 2012 was completed. Presence of GERD and VUR were ascertained based on billing codes. The baseline prevalence of GERD and VUR was calculated for this population for the same time period. Proportions of VUR patients with and without GERD were compared. The risk of being diagnosed with VUR in patients with GERD controlling for sex was calculated. RESULTS: Of 404 300 patients identified, 6.6% had a diagnosis of GERD (n=27 092), 0.33% had a diagnosis of VUR (n=1348), and 0.08% were diagnosed with both (n=327). Among patients with VUR, the prevalence of GERD was 24.3% compared to 6.6% in patients without VUR (p<0.0001). Among patients with GERD, the prevalence of VUR was 1.2% compared to 0.27% in patients without (p<0.0001). The risk of being diagnosed with VUR was higher in the presence of GERD (odds ratio [OR] 4.49; 95% confidence interval [CI] 3.96–5.09; p<0.0001), irrespective of sex. CONCLUSIONS: The odds of being diagnosed with VUR is more than 4.5 times higher in an individual with GERD. The clinical significance of this association remains to be explored.